Teaching Complex Adaptive Systems Science in Natural Resource Management: Examples from Forestry. Issue 1 (20th December 2016) - Puettmann, Klaus J.; Parrott, Lael; Messier, Christian
Abstract : Core Ideas: Complexity science brings some very useful novel concepts to natural resource management that are important to sustainability. Yet, these concepts are rarely taught to graduate students in terms of how they practically can be used in natural resource management settings. We present a series of field exercises that have shown promise in introducing complexity science to graduate students in forest management programs and may be adapted by instructors to suit a variety of teaching contexts. Teaching theoretical concepts, such as complexity theory, provides unique challenges, especially in applied disciplines. Current trends such as global change will require natural resource disciplines, for example forestry and agriculture, to expand their scientific basis and possibly shift their dominant paradigms to adopt a broader view of the ecosystems they manage as complex social‐ecological systems. This likely will result in borrowing and adapting theories and concepts from other disciplines such as complexity science. Students in natural resources will need more training in these paradigms and learn to incorporate concepts such as thresholds, uncertainty, and cross‐scale interactions as they affect ecosystem dynamics and thus management or restoration prescriptions. Numerous courses and approaches exist that teach general complexity concepts, including management implications at the governance levels. However, we do not know of any courses where these concepts are specifically applied to practical management challenges. This article aims to overcome this shortcoming by sharing our experiences. Specifically, we provide examples of field exercises that can be used to link theoretical concepts from complexity science to applied forest management issues, regardless of management objectives. Instructors are encouraged to evaluate these examples and modify them as necessary for uses in graduate classes and workshops. We hope that these exercises will help expose graduate students and professionals to a wider range of theories and concepts.